Disruptive Innovation-Based Model of Sustainable Competitiveness Development in Small and Medium Food Industries - Taneo, Stefanus Yufra M.; Noya, Sunday; Setiyati, Etsa Astridya; Melany, Melany (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 13 Nomor 2 Tahun 2019DO - 10.24843/MATRIK:JMBK.2019.v13.i02.p03, 2019)
Small and Medium Food Industries (SMFIs) play an important role in the national economy but its competitiveness is low due to the limited innovation applied by business managers. Current innovation research is partial and excludes disruptive innovation and sustainable competitiveness. This research fills the gap by developing a model for increasing the competitiveness of SMFIs based on disruptive innovation and identifying constraints faced by SMFIs if the model is implemented. Data was collected through Focus Group Discussions and surveys using questionnaires. With a model framework approach, the model is composed of six subsystems, namely input, production process, post production, marketing, and supporting institutions. The potential for disruptive innovation lies in the quality of functional food products and low production costs because resources are available locally. However, the potential for disruptive innovation has not been utilized optimally by SMFI due to various obstacles. The role of government is very important to optimize the competitiveness potential of SMFI.